Perlindungan Hukum terhadap Istri dalam Perkawinan Poligami di Provinsi Riau - Kholid, Andre; Akbarizan, Akbarizan; Munir, Akmal Abdul (Jurnal El-Thawalib, 2025)
Legal protection for wives in the context of polygamy is important to examine, considering that not all polygamy practices are carried out in accordance with applicable legal provisions. In addition, the existence of strong Islamic legal norms and customary norms in Riau Province also influences the views and implementation of polygamy in society. The purpose of this study is to determine the form of legal protection for wives in polygamous practices in Riau Province. This type of research is qualitative research. Primary data sources were obtained through interviews with wives of polygamists, husbands, community leaders, and religious and legal institutions. Secondary data comes from official documents, legal literature, laws and regulations, and previous research results. Data collection techniques are interviews and documentation, then analyzed using analytical descriptive techniques. The results of this study indicate that legal protection for wives in polygamous marriages in Riau Province involves two main aspects, namely preventive and repressive protection. Preventive protection is realized through strict requirements, such as the consent of the first wife and court permission before carrying out polygamy, to ensure that the wife's rights are maintained. Meanwhile, repressive protection provides a legal mechanism for wives who are harmed, such as the cancellation of an invalid marriage. Overall, Indonesian law provides guarantees for wives in polygamous marriages to ensure justice and protection of their rights.